Moderasi Fatwa: Telaah Kritis atas Keputusan Fatwa Majelis Ulama Indonesia Provinsi Jambi tentang Pengalihan Harta Wakaf - Sibawaihi, Muhammad; Yuliatin, Yuliatin; Naziro, Naziro (Al-Qisthu, 2024)
In 2021, the Indonesian Council of Ulama (MUI) of Jambi Province issued a fatwa permitting the transfer, exchange, or alteration of waqf assets to enhance their value and utility. This stands in contrast to the Shafi’i school of thought, which is predominantly followed by Muslims in Indonesia, where such actions are generally discouraged. This study aims to explore the legal methodology employed by the MUI of Jambi Province and to elucidate the principles of religious moderation inherent in their decision. The research utilizes a case study design, relying on interview data from MUI officials and document analysis of the issued fatwa and other relevant materials. The findings indicate that, although this fatwa initially appears to contradict the Shafi’i doctrine, it is procedurally sound, employing the methodologies of bayani, ta’lili, and istishlahi. Substantively, it aligns with the Quran, Hadith, and the views of both classical and contemporary scholars, strongly supporting the principle of public interest (maslahah). Moreover, the fatwa reflects significant aspects of religious moderation, particularly inclusivity, respect for tradition, and adaptability to social change.